Social management responsiveness in business - Saenz, Cesar (Emerald Publishing Limited, 2023)
A lot of controversy exists around the contribution of the mining industry and the territorial development of the regions where it operates. Despite the boom in mineral prices, there are still many communities that do not show development. At the macroeconomic level, countries with a mining industry receive income from mining taxes and royalties, however, at the micro level this greater income is not reflected in the closing of socio-economic gaps and the well-being of the population. Cesar Saenz presents the Social Management Model Canvas (SMMC), describing the rationale of how an extractive company can create and deliver social value for communities around and beyond the sphere of influence. The SMMC can best be described through nine basic building blocks - the social value proposition; defining the community; social channels; relationship with the community; key social resources; key social activities; key social partners; social investment structure and social benefits. Companies can map the existing social management model to visualize, understand and communicate the level of responsiveness of the model, whilst using the canvas to explore new social management improvements to get a social license to operate. Communities require companies and governments to address their needs such as education, employment, health service, among others. Combining all these elements in a social management model helps companies consider all the variables when designing and implementing strategies that meet both business and community needs.
Keywords: Social responsibility of business.; Mines and mineral resources -- Social aspects.; Business & Economics -- Business Ethics.; Business ethics & social responsibility.; elektronické knihy; electronic books